Cognitive approach of using Code- Switching for the Monoculture Students with English as a Second Language (ESL) - V, Parvathy.; Pillai, Radharemanan (International Journal of Psychosocial Rehabilitation, 2020)
This paper concentrates on the effective ways of adapting code-switching in the classroom for socially backward Indian students with minimal exposure to English as Second Language (ESL). Various forms of code-switching are analysed with the objective of understanding the most effective provision of transferring knowledge to these students. In this effort the role of the teachers and the student-centric cognitive approaches are analysed with in-depth understanding.In a way this paper illustrate the ways of using code-switching in a monocultural learning and teaching environment, so that the students can gain maximum subject oriented concepts.